2010
DOI: 10.1373/clinchem.2009.140194
|View full text |Cite
|
Sign up to set email alerts
|

Report of the IFCC Working Group for Standardization of Thyroid Function Tests; Part 2: Free Thyroxine and Free Triiodothyronine

Abstract: BACKGROUND:Free thyroxine (FT4) and free triiodothyronine (FT3) measurements are useful in the diagnosis and treatment of a variety of thyroid disorders. The IFCC Scientific Division established a Working Group to resolve issues of method performance to meet clinical requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 7 publications
2
96
0
2
Order By: Relevance
“…This assay has proven to give comparable results with other assays, according to the report from the IFCC WG for standardization of thyroid function tests (17).…”
Section: Biochemical Determinationsmentioning
confidence: 78%
“…This assay has proven to give comparable results with other assays, according to the report from the IFCC WG for standardization of thyroid function tests (17).…”
Section: Biochemical Determinationsmentioning
confidence: 78%
“…44 To address this important issue, a working group for the international standardization of the free T4 assay has been formed. [45][46][47] Thus, if the assessment of free T4 may not be necessary in many cases (low pre-test probability), and the reliability is limited, there is likely to be a substantial number of false-positive results.…”
Section: Free Thyroxine (Free T4)mentioning
confidence: 99%
“…43,44,47 Measurement of free T4 by equilibrium dialysis is considered the gold standard but, it is of limited availability to most providers. There is good correlation of free T4 by equilibrium dialysis and free T4 by liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Free Thyroxine (Free T4)mentioning
confidence: 99%
“…This protocol has also been validated to be suitable for triglycerides and HDL cholesterol (15 ) and for creatinine (16 ). The C37A protocol has not been validated to produce samples that are commutable with patient samples for other analytes but represents the best available approach and has been used to prepare single-donor serum samples and pools for several investigations of the trueness of measurement procedures for several analytes (17)(18)(19)(20)(21). Thienpont et al found that processing of serum (e.g., sterile filtration, storage before aliquoting and freezing) may disturb the equilibrium between free and protein-bound thyroid hormone and hence jeopardize the commutability of a reference material prepared even from sera that has been subjected to minimal processing (22 ).…”
Section: Preparation Of Samples Intended To Be Commutablementioning
confidence: 99%